2016
DOI: 10.1063/1.4968613
|View full text |Cite
|
Sign up to set email alerts
|

Detecting thermal rectification

Abstract: Thermal rectification is a special heat transfer phenomenon that thermal conductance of a sample is higher in one direction than that in the reversed direction. Thermal rectifiers have been proposed to be the building blocks of phononic circuits, high performance thermoelectric devices, and energy-saving materials. Theoretically, thermal rectification has been suggested to be ubiquitous, occurring in wherever nonlinear interactions and broken inversion symmetry are present. However, currently available experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…At φ = 18% the pores are uniformly distributed throughout the simulation domain and no rectification is observed. Thus, structural asymmetry in the transport direction (x-direction) gives rise to thermal rectification as also observed in previous theoretical [16,17,20] and experimental works [30,31]. In Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…At φ = 18% the pores are uniformly distributed throughout the simulation domain and no rectification is observed. Thus, structural asymmetry in the transport direction (x-direction) gives rise to thermal rectification as also observed in previous theoretical [16,17,20] and experimental works [30,31]. In Fig.…”
Section: Resultssupporting
confidence: 83%
“…Recently, significant research has been done on understanding and controlling phonon transport in nanostructures for novel materials and applications [1][2][3][4][5][6][7][8]. Since initial findings of thermal rectification between Cu and Cu2O [9] interfaces in the 1930s, various experimental [10][11][12] and theoretical [13][14][15][16][17][18][19][20][21] studies have investigated thermal rectification in different materials. Rectification values of up to 350% were theoretically predicted in graphene nanoribbons [22], while experiments showed that graphene junctions could provide even higher values of up to 800% rectification [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancement for Q + /Qhas been commonly considered by introducing a structural asymmetry in the system yielding an asymmetric phonon transport. Till date, mass-loading [6][7][8], nanostructure embedded interface [9,10], and shape asymmetric tapered (tailored) nanomaterials [10][11][12][13][14][15][16] and networks [17] have been studied so far. Measured γ TR values are mostly less than 40% and usually smaller than theoretical predictions (references are therein Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Because Q e,B is insensitive to the variation of ∆T , the behavior of R r is very similar to Q e,F . To design HDs, one needs to have a high R r at a small temperature bias [39]. Fig.…”
Section: Electron Heat Rectificationmentioning
confidence: 99%